The Effects of Cultural Practices on Cognitive and Memory Development in Malawian Children: An Examination of Play, Screen Time, and Storytelling Traditions. - Kayira, Mike (Universitas Muhammadiyah Surakarta, 2024)
Using secondary techniques, this study looks into the impact of cultural practices regarding play and screen time on cognitive development, as well as the relationship between cultural storytelling practices and memory development in Malawian children. The methodology consists of an in-depth literature review, secondary data analysis, meta-analysis, and content analysis. The data show that traditional play is highly valued in Malawi, positively impacting cognitive and social development, whereas increased screen usage, particularly in urban areas, has mixed cognitive outcomes. Data from national assessments and international surveys demonstrate that traditional play correlates with higher academic success, whereas excessive screen usage is associated with shorter attention spans and lower academic performance. Educational resources and policy documents emphasize the benefits of traditional play, but they lack detailed guidance for controlling screen use.Furthermore, the study investigates the link between storytelling traditions and memory formation. According to research, storytelling is extremely important in Malawian culture, and frequent storytelling activities dramatically improve memory recall and comprehension. Traditional folktales with intricate narratives and character arcs encourage cognitive engagement and memory formation. Comparative studies show that storytelling generally promotes cognitive development, but the exact effects differ by culture, with Malawian customs providing distinct cognitive demands.The study emphasises the need to incorporate storytelling into educational courses and blend traditional play with modern screen usage to promote cognitive development. Future studies should concentrate on focused interventions that maximise the benefits of cultural traditions within modern educational systems. This approach gives a strong foundation for understanding the specific objectives without the requirement for